Does Growth Mindset escalate Organizational Citizenship Behavior and Goal Achievement? A mediating role of Work Engagement and a moderating role of Transformational Leadership - Imran, Naila; Akbar, Waqar; Khan, Saba; Usman, 4Asna; Usman, 4Asna; Mansoor, Mehreen (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to understand the impact of Growth Mindset on Goal Achievement and Organizational Citizenship Behavior with a mediating role of work engagement and the moderating role of transformational leadership. 278 knowledge workers participated in the study by filling the self-administrated questionnaire from Pakistan. Data analysis was done through partial least square structural equation modeling (PLS-SEM) technique. The results find a positive impact of growth mindset on Goal achievement and Organizational Citizenship Behavior and the significant mediating effect of work engagement. The study also highlights the potent role of transformational leadership as a moderator and proposes that in the absence of Transformational Leadership, growth mindset alone is not sufficient enough. The study advances the literature on growth mindset which may help the managers to understand the mindset of their employees for improving individual and organizational achievement. It also helps the managers and supervisors to understand their role as a leader in cultivating and promoting the growth mindset of their employees. Avenues for future research are also suggested.